Pre-service teachers' self-efficacy towards children with disabilities: An Irish perspective - Tindall, Daniel; Culhane, Maeve; Foley, T. John (European Journal of Adapted Physical Activity, 2016)
The purpose of this study was to examine the effects of a 10-week adapted physical activity (APA) programme on the self-efficacy levels of pre-service teachers (PSTs) towards teaching children and young people with disabilities (ages 5 to 21) during a weekly 1-hour APA programme. Participants included 64 PSTs (ages 19-25) in their 3rd year of a physical education initial teacher education (PE-ITE) programme at a university within the Republic of Ireland. PSTs completed the Self-Efficacy Scale for Physical Education Teacher Education Majors toward Children with Disabilities (SE-PETE-D) questionnaire both before and after their participation in the APA programme followed by a focus group interview (n=4). Repeated-measure ANOVAs showed that self-efficacy scores significantly increased after participation in the programme than those prior to participation in the programme. Results of the focus group discussion also confirmed the findings from the questionnaire to be true and accurate.
Keywords: self-efficacy; physical education initial teacher education; adapted physical activity